Nano styrene-butadiene latex flexibilizer, high-temperature-resistant and carbon dioxide corrosion-resistant cement paste and preparation method thereof
The high-temperature, carbon dioxide corrosion-resistant cement slurry prepared with nanostyrene butadiene latex toughening agent solves the problem of existing cement failure in high temperature and carbon dioxide environment, and achieves the effect of improving cement strength, reducing permeability and increasing elasticity.
Patent Information
- Application Number
- CN202311202830.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-18
- Publication Date
- 2025-03-18
AI Technical Summary
Existing cement cement is prone to failure in high temperature and carbon dioxide corrosion environments, and cannot effectively seal carbon dioxide for a long time, affecting the cementing quality.
Nanobutylbutane latex toughening agent is used as raw material to prepare high-temperature and carbon dioxide corrosion-resistant cement slurry, which prevents carbon dioxide corrosion by increasing the strength of cement stone, reducing permeability, and increasing elasticity.
The strength of the first and second cementing surfaces of the cement cement ring is significantly improved, the permeability of cement stone is reduced, the corrosion of carbon dioxide is prevented, the elasticity of cement stone is increased, and the risk of fracture in perforation and fracturing operations is reduced.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cement slurry, in particular to a nano-styrene-butadiene latex toughening agent and a preparation method thereof, and also comprises high temperature resistant and carbon dioxide corrosion resistant cement slurry and a preparation method thereof. Background Art
[0002] Carbon capture and storage (CCS) combines carbon dioxide with oil production engineering, sealing liquid carbon dioxide into the formation during the cementing process. It has very high requirements for the quality of oil well cementing, and the most intuitive requirement is reflected in the cementing cement. The main components of conventional cementing cement are alkaline substances. High concentrations of carbon dioxide and their aqueous solutions will cause varying degrees of corrosion to the solidified cement stone, causing cement failure, resulting in the inability to effectively seal carbon dioxide for a long time and the inability to complete subsequent work.
[0003] Nano-silicon dioxide is an inorganic chemical material, commonly known as white carbon black. As it is ultra-fine nano-scale, with a size range of 1nm to 100nm, it has many unique properties, such as optical properties against ultraviolet rays, and can improve the anti-aging, strength and chemical resistance of other materials, and has a wide range of uses. Summary of the invention
[0004] The invention provides a nano-styrene butadiene latex toughening agent, a high-temperature resistant and carbon dioxide corrosion resistant cement slurry and a preparation method thereof, which overcomes the above-mentioned shortcomings of the prior art. The high-temperature resistant and carbon dioxide corrosion resistant cement slurry prepared by the invention can not only improve the strength of the first and second cementing surfaces of the cement ring, reduce the permeability of cement stone, and prevent carbon dioxide from corroding the cement stone, but also increase the elasticity and toughness of the cement stone.
[0005] One of the technical solutions of the present invention is achieved through the following measures: a nano-styrene butadiene latex toughening agent, wherein the raw materials include 20 to 70 parts of styrene, 5 to 30 parts of 2-acrylamide-2-methylpropane sulfonic acid, 20 to 70 parts of polybutadiene, 5 to 20 parts of modified nano-silica, 0.5 to 5.0 parts of sodium dodecyl sulfate, 0.5 to 3.0 parts of initiator and 0.2 to 1.0 parts of molecular weight regulator in parts by weight.
[0006] The following is a further optimization and / or improvement of one of the above-mentioned technical solutions: The nano-styrene-butadiene latex toughening agent is obtained by the following method: S1, mixing required amounts of styrene, 2-acrylamide-2-methylpropanesulfonic acid and water to obtain a temperature-resistant monomer pre-emulsion; S2, mixing required amounts of polybutadiene, modified nano-silica and water to obtain a toughening monomer pre-emulsion; S3, mixing a required amount of molecular weight regulator with water to obtain a molecular regulator solution, adding a portion of the temperature-resistant monomer pre-emulsion and a portion of the toughening monomer pre-emulsion to the molecular regulator solution, mixing and reacting to obtain an emulsion seed; S4, adding the remaining amount of the temperature-resistant monomer pre-emulsion, the remaining amount of the toughening monomer pre-emulsion and the required amount of the initiator to the emulsion seed, mixing and reacting to obtain a reaction product; S5, washing the reaction product with anhydrous ethanol, drying, and crushing to obtain a nano-styrene-butadiene latex toughening agent.
[0007] The molecular regulator is dodecanethiol, and the initiator is one of ammonium persulfate, potassium persulfate, sodium persulfate and acetic anhydride.
[0008] In the above step S1, the mass concentration of the monomers (styrene and 2-acrylamide-2-methylpropanesulfonic acid) in the temperature-resistant monomer pre-emulsion is 15% to 40%.
[0009] In the above step S2, the mass concentration of the monomers (polybutadiene and modified nano-silica) in the toughening monomer pre-emulsion is 15% to 45%.
[0010] In the above step S3, a portion of the temperature-resistant monomer pre-emulsion accounts for 4% to 6% of the total weight of the temperature-resistant monomer pre-emulsion, a portion of the toughening monomer pre-emulsion accounts for 4% to 6% of the total weight of the toughening monomer pre-emulsion, and the mass concentration of the molecular regulator solution is 1%.
[0011] In the above step S3, the reaction time is 0.4h to 0.6h, and the reaction temperature is 55°C to 65°C.
[0012] In the above step S4, the reaction time is 3.5 h to 4.5 h, and the reaction temperature is 60° C. to 70° C.
[0013] The second technical solution of the present invention is achieved by the following measures: a preparation method of a nano-styrene butadiene latex toughening agent is carried out as follows: S1, mixing required amounts of styrene, 2-acrylamide-2-methylpropanesulfonic acid and water to obtain a temperature-resistant monomer pre-emulsion; S2, mixing required amounts of polybutadiene, modified nano-silica and water to obtain a toughening monomer pre-emulsion; S3, mixing a required amount of molecular weight regulator with water to obtain a molecular regulator solution, adding a portion of the temperature-resistant monomer pre-emulsion and a portion of the toughening monomer pre-emulsion to the molecular regulator solution, mixing and reacting to obtain an emulsion seed; S4, adding the remaining amount of the temperature-resistant monomer pre-emulsion, the remaining amount of the toughening monomer pre-emulsion and the required amount of the initiator to the emulsion seed, mixing and reacting to obtain a reaction product; S5, washing the reaction product with anhydrous ethanol, drying, and crushing to obtain a nano-styrene-butadiene latex toughening agent.
[0014] The third technical solution of the present invention is achieved through the following measures: a high temperature resistant and carbon dioxide corrosion resistant cement slurry prepared with one of the technical solutions as raw materials, the raw materials including 600 to 700 parts of G-grade cement, 100 to 200 parts of slag powder, 10 to 50 parts of whiskers, 10 to 50 parts of polymer fibers, 10 to 50 parts of fly ash, 10 to 50 parts of microsilica powder, 10 to 50 parts of nano-styrene-butadiene latex toughening agent, 10 to 50 parts of dispersant, 30 to 60 parts of fluid loss reducer, 10 to 30 parts of expansion agent, 20 to 50 parts of early strength agent, 10 to 20 parts of defoaming agent and 0 to 5 parts of retarder.
[0015] The following is a further optimization and / or improvement of the third technical solution of the above invention: The above-mentioned cement slurry resistant to high temperature and corrosion by carbon dioxide is obtained by the following method: In the first step, required amounts of whiskers and polymer fibers are respectively mixed with water to obtain whisker suspensions and polymer fiber suspensions; The second step is to add water to the required amount of fluid loss reducer, nano-styrene butadiene latex toughening agent and defoamer to mix to obtain a mixed emulsion; The third step is to add the whisker suspension, the polymer fiber suspension and 40 to 55 parts of water into the mixed emulsion under stirring and mix them evenly to obtain a mixed wet material; The fourth step is to add the required amount of G-grade cement, slag powder, fly ash, microsilica powder, dispersant, expansion agent, early strength agent and retarder to the mixed wet material in sequence under stirring, mix evenly, and then after high-speed stirring, obtain cement slurry that is resistant to high temperature and carbon dioxide corrosion.
[0016] In the first step, the mass concentration of the whisker suspension is 3% to 5%, and the mass concentration of the polymer fiber suspension is 0.5% to 2.0%.
[0017] In the second step, the mass concentration of the solute (fluid loss reducer, nano-styrene-butadiene latex toughening agent and defoaming agent) in the mixed emulsion is 8% to 15%.
[0018] In the third step, the stirring rate is 4000 r / min.
[0019] In the fourth step, the stirring rate is 6000 r / min during stirring, and the stirring rate is 12000 r / min during high-speed stirring, and the stirring time is 1 min to 5 min.
[0020] The fourth technical solution of the present invention is achieved by the following measures: A method for preparing a cement slurry resistant to high temperature and carbon dioxide corrosion is carried out according to the following method: In the first step, required amounts of whiskers and polymer fibers are respectively mixed with water to obtain whisker suspensions and polymer fiber suspensions; The second step is to add water to the required amount of fluid loss reducer, nano-styrene butadiene latex toughening agent and defoamer to mix to obtain a mixed emulsion; The third step is to add the whisker suspension, the polymer fiber suspension and 40 to 55 parts of water into the mixed emulsion under stirring and mix them evenly to obtain a mixed wet material; The fourth step is to add the required amount of G-grade cement, slag powder, fly ash, microsilica powder, dispersant, expansion agent, early strength agent and retarder to the mixed wet material in sequence under stirring, mix evenly, and then after high-speed stirring, obtain cement slurry that is resistant to high temperature and carbon dioxide corrosion.
[0021] The high temperature resistant and carbon dioxide corrosion resistant cement slurry prepared by using nano-styrene butadiene latex toughening agent as raw material can improve the strength of the first and second cementing surfaces of cement ring, reduce the permeability of cement stone, prevent carbon dioxide from corroding cement stone, and at the same time increase the elastic toughness of cement stone, and reduce the degree of fracture of cement stone in subsequent cementing operations such as perforation and fracturing. DETAILED DESCRIPTION
[0022] The present invention is not limited by the following embodiments, and specific implementation methods can be determined according to the technical scheme of the present invention and actual conditions. Unless otherwise specified, the various chemical reagents and chemicals mentioned in the present invention are all known and commonly used chemical reagents and chemicals in the prior art; the percentages in the present invention are all mass percentages unless otherwise specified.
[0023] The present invention will be further described below in conjunction with embodiments: Embodiment 1: The nano-styrene butadiene latex toughening agent comprises, by weight, 20 to 70 parts of styrene, 5 to 30 parts of 2-acrylamide-2-methylpropane sulfonic acid, 20 to 70 parts of polybutadiene, 5 to 20 parts of modified nano-silica, 0.5 to 5.0 parts of sodium dodecyl sulfate, 0.5 to 3.0 parts of initiator and 0.2 to 1.0 parts of molecular weight regulator.
[0024] Embodiment 2: As the optimization of the above embodiment, the nano-styrene butadiene latex toughening agent is obtained by the following method: S1, mixing required amounts of styrene, 2-acrylamide-2-methylpropanesulfonic acid and water to obtain a temperature-resistant monomer pre-emulsion; S2, mixing required amounts of polybutadiene, modified nano-silica and water to obtain a toughening monomer pre-emulsion; S3, mixing a required amount of molecular weight regulator with water to obtain a molecular regulator solution, adding a portion of the temperature-resistant monomer pre-emulsion and a portion of the toughening monomer pre-emulsion to the molecular regulator solution, mixing and reacting to obtain an emulsion seed; S4, adding the remaining amount of the temperature-resistant monomer pre-emulsion, the remaining amount of the toughening monomer pre-emulsion and the required amount of the initiator to the emulsion seed, mixing and reacting to obtain a reaction product; S5, washing the reaction product with anhydrous ethanol, drying, and crushing to obtain a nano-styrene-butadiene latex toughening agent.
[0025] Example 3: As an optimization of the above example, the molecular regulator is dodecanethiol, and the initiator is one of ammonium persulfate, potassium persulfate, sodium persulfate and acetic anhydride.
[0026] Example 4: As an optimization of the above example, in step S1, the mass concentration of the monomers (styrene and 2-acrylamide-2-methylpropanesulfonic acid) in the temperature-resistant monomer pre-emulsion is 15% to 40%.
[0027] Example 5: As an optimization of the above example, in step S2, the mass concentration of the monomers (polybutadiene and modified nano-silica) in the toughening monomer pre-emulsion is 15% to 45%.
[0028] Example 6: As an optimization of the above example, in step S3, a portion of the temperature-resistant monomer pre-emulsion accounts for 4% to 6% of the total weight of the temperature-resistant monomer pre-emulsion, a portion of the toughening monomer pre-emulsion accounts for 4% to 6% of the total weight of the toughening monomer pre-emulsion, and the mass concentration of the molecular regulator solution is 1%.
[0029] Example 7: As an optimization of the above example, in step S3, the reaction time is 0.4h to 0.6h, and the reaction temperature is 55°C to 65°C.
[0030] Example 8: As an optimization of the above example, in step S4, the reaction time is 3.5 h to 4.5 h, and the reaction temperature is 60°C to 70°C.
[0031] Compared with existing cementing latex products, the nano-styrene butadiene latex toughening agent of the present invention has the following beneficial effects: First, the nano-styrene butadiene latex toughening agent of the present invention has a good thickening effect on the system after being added to the cement slurry, and has the characteristics of blocking pores and easy film formation, which can reduce the filtration loss of the cement slurry, has film-forming properties and non-permeability, and can prevent the occurrence of gas channeling; Second, after being added into cement slurry, the nano-styrene butadiene latex toughening agent of the present invention can reduce the volume shrinkage of cement sheath and improve the bonding between cement sheath, casing and formation; Third, after being added to cement slurry, the nano-styrene butadiene latex toughening agent of the present invention fills the fine pores inside the cement stone, reduces the permeability of the cement stone, and prevents CO2 from invading the pores; Fourthly, after being added into cement paste, the nano-styrene butadiene latex toughening agent of the present invention forms a continuous network structure on the surface and inside of cement paste, thereby enhancing the connectivity of different parts of cement paste, preventing the cracking of cement paste caused by CO2 corrosion, and improving the corrosion resistance and durability of cement paste.
[0032] Example 9: As an optimization of the above example, a high temperature resistant and carbon dioxide corrosion resistant cement slurry is obtained with the nano-styrene butadiene latex toughening agent described in the above example as raw material, wherein the raw materials include, by weight, 600 to 700 parts of G-grade cement, 100 to 200 parts of slag powder, 10 to 50 parts of whiskers, 10 to 50 parts of polymer fibers, 10 to 50 parts of fly ash, 10 to 50 parts of microsilica powder, 10 to 50 parts of nano-styrene butadiene latex toughening agent, 10 to 50 parts of dispersant, 30 to 60 parts of fluid loss additive, 10 to 30 parts of expansion agent, 20 to 50 parts of early strength agent, 10 to 20 parts of defoaming agent and 0 to 5 parts of retarder.
[0033] In the present invention, the dispersant is dispersant USZ, the fluid loss agent is fluid loss agent BXF-200 L, the expander is expander QJ-625, the early strength agent is early strength agent G209, the defoamer is defoamer BP-1B, and the retarder is retarder HT-R.
[0034] Example 10: As an optimization of the above example, a cement slurry resistant to high temperature and carbon dioxide corrosion is obtained by the following method: In the first step, required amounts of whiskers and polymer fibers are respectively mixed with water to obtain whisker suspensions and polymer fiber suspensions; The second step is to add water to the required amount of fluid loss reducer, nano-styrene butadiene latex toughening agent and defoamer to mix to obtain a mixed emulsion; The third step is to add the whisker suspension, the polymer fiber suspension and 40 to 55 parts of water into the mixed emulsion under stirring and mix them evenly to obtain a mixed wet material; The fourth step is to add the required amount of G-grade cement, slag powder, fly ash, microsilica powder, dispersant, expansion agent, early strength agent and retarder to the mixed wet material in sequence under stirring, mix evenly, and then after high-speed stirring, obtain cement slurry that is resistant to high temperature and carbon dioxide corrosion.
[0035] Example 11: As an optimization of the above example, in the first step, the mass concentration of the whisker suspension is 3% to 5%, and the mass concentration of the polymer fiber suspension is 0.5% to 2.0%.
[0036] Example 12: As an optimization of the above example, in the second step, the mass concentration of the solute (fluid loss reducer, nano-styrene butadiene latex toughening agent and defoaming agent) in the mixed emulsion is 8% to 15%.
[0037] Example 13: As an optimization of the above example, in the third step, during stirring, the stirring rate is 4000 r / min.
[0038] Example 14: As an optimization of the above example, in the fourth step, during stirring, the stirring rate is 6000 r / min, during high-speed stirring, the stirring rate is 12000 r / min, and the stirring time is 1 min to 5 min.
[0039] The beneficial effects of the high temperature resistant and carbon dioxide corrosion resistant cement slurry prepared by using the nano-styrene butadiene latex toughening agent of the present invention as a raw material are: First, the high temperature resistant and carbon dioxide corrosion resistant cement slurry prepared by the present invention can significantly reduce its filtration loss, ensuring that there will be no excessive liquid separation during the flow of cement slurry in the wellbore, and no gas channeling will occur; Second, the high temperature resistant and carbon dioxide corrosion resistant cement slurry prepared by the present invention can greatly improve the mechanical properties of cement paste, especially in terms of compressive strength and tensile strength. The formed cement paste has low permeability and is dense, which can reduce the fracture degree of cement sheath during perforation. Thirdly, the high temperature resistant and carbon dioxide corrosion resistant cement slurry prepared by the present invention can promote the integrity of the cement stone hydration process. The internal cross-linked network structure of the raw material nano-styrene butadiene latex toughening agent can ensure the progress of the internal hydration process of the cement stone and the formation of the strength of the cement stone. At the same time, inorganic materials such as microsilica powder and polymer fibers can be effectively dispersed in various parts of the cement stone, ensuring that the surface of the cement stone has sufficient mechanical strength, reducing the formation of hydration pores, and reducing the intrusion of CO2 wet environment; Fourthly, the high temperature resistant and CO2 corrosion resistant cement slurry of the present invention has good construction performance. The high temperature resistant and CO2 corrosion resistant cement slurry system of the present invention has low initial consistency and adjustable thickening time, and can maintain good flow properties within the thickening time.
[0040] Embodiment 15: The nano-styrene butadiene latex toughening agent comprises, by weight, 20 parts of styrene, 5 parts of 2-acrylamide-2-methylpropane sulfonic acid, 20 parts of polybutadiene, 5 parts of modified nano-silicon dioxide, 0.5 parts of sodium dodecyl sulfate, 0.5 parts of initiator and 0.2 parts of dodecyl mercaptan, and is obtained by the following method: S1, mixing the required amount of styrene, 2-acrylamide-2-methylpropane sulfonic acid and water to obtain a temperature-resistant monomer pre-emulsion; wherein the mass concentration of the monomers (styrene and 2-acrylamide-2-methylpropane sulfonic acid) in the temperature-resistant monomer pre-emulsion is 15%; S2, mixing the required amount of polybutadiene, modified nano-silica and water to obtain a toughening monomer pre-emulsion; wherein the mass concentration of the monomers (polybutadiene and modified nano-silica) in the toughening monomer pre-emulsion is 15%; S3, mixing a required amount of dodecanethiol with water to obtain a dodecanethiol solution with a mass concentration of 1%, adding 4% of the heat-resistant monomer pre-emulsion accounting for the total weight of the heat-resistant monomer pre-emulsion and 4% of the toughening monomer pre-emulsion accounting for the total weight of the toughening monomer pre-emulsion to the dodecanethiol solution with a vector concentration of 1%, mixing, reacting at 55° C. for 0.4 h, to obtain an emulsion seed; S4, adding the remaining amount of the temperature-resistant monomer pre-emulsion, the remaining amount of the toughening monomer pre-emulsion and the required amount of ammonium persulfate to the emulsion seed, and reacting at 60° C. for 3.5 hours to obtain a reaction product; S5, washing the reaction product with anhydrous ethanol, drying, and crushing to obtain a nano-styrene-butadiene latex toughening agent.
[0041] The high temperature resistant and carbon dioxide corrosion resistant cement slurry comprises, by weight, 600 parts of G-grade cement, 100 parts of slag powder, 10 parts of whiskers, 10 parts of polymer fibers, 10 parts of fly ash, 10 parts of microsilica powder, 10 parts of nano-styrene-butadiene latex toughening agent, 10 parts of dispersant, 30 parts of fluid loss reducer, 10 parts of expansion agent, 20 parts of early strength agent, 10 parts of defoamer and 1 part of retarder, and is obtained by the following method: In the first step, required amounts of whiskers and polymer fibers are respectively mixed with water to obtain a whisker suspension with a mass concentration of 3% and a polymer fiber suspension with a mass concentration of 0.5%; The second step is to add water to the required amount of fluid loss reducer, nano-styrene butadiene latex toughening agent and defoamer to mix to obtain a mixed emulsion; The third step is to add the whisker suspension, the polymer fiber suspension and 40 parts of water into the mixed emulsion at a stirring rate of 4000 r / min and mix them evenly to obtain a mixed wet material; wherein the mass concentration of the solute (fluid loss reducer, nano-styrene butadiene latex toughening agent and defoaming agent) in the mixed emulsion is 8%; The fourth step is to add the required amount of Grade G cement, slag powder, fly ash, microsilica powder, dispersant, expansion agent, early strength agent and retarder to the mixed wet material in sequence at a stirring rate of 6000r / min, mix them evenly, and then stir for 1 minute at a stirring rate of 12000r / min to obtain cement slurry that is resistant to high temperature and carbon dioxide corrosion.
[0042] Embodiment 16: The nano-styrene butadiene latex toughening agent comprises, by weight, 70 parts of styrene, 30 parts of 2-acrylamide-2-methylpropane sulfonic acid, 70 parts of polybutadiene, 20 parts of modified nano-silicon dioxide, 5.0 parts of sodium dodecyl sulfate, 3.0 parts of initiator and 1.0 part of dodecyl mercaptan, and is obtained by the following method: S1, mixing the required amount of styrene, 2-acrylamide-2-methylpropane sulfonic acid and water to obtain a temperature-resistant monomer pre-emulsion; wherein the mass concentration of the monomers (styrene and 2-acrylamide-2-methylpropane sulfonic acid) in the temperature-resistant monomer pre-emulsion is 40%; S2, mixing the required amount of polybutadiene, modified nano-silica and water to obtain a toughening monomer pre-emulsion; wherein the mass concentration of the monomers (polybutadiene and modified nano-silica) in the toughening monomer pre-emulsion is 45%; S3, mixing a required amount of dodecanethiol with water to obtain a dodecanethiol solution with a mass concentration of 1%, adding 6% of the heat-resistant monomer pre-emulsion accounting for the total weight of the heat-resistant monomer pre-emulsion and 6% of the toughening monomer pre-emulsion accounting for the total weight of the toughening monomer pre-emulsion to the dodecanethiol solution with a vector concentration of 1%, mixing, reacting at 65° C. for 0.6 h, to obtain an emulsion seed; S4, adding the remaining amount of the temperature-resistant monomer pre-emulsion, the remaining amount of the toughening monomer pre-emulsion and the required amount of ammonium persulfate to the emulsion seed, and reacting at 70° C. for 4.5 hours to obtain a reaction product; S5, washing the reaction product with anhydrous ethanol, drying, and crushing to obtain a nano-styrene-butadiene latex toughening agent.
[0043] The high temperature resistant and carbon dioxide corrosion resistant cement slurry comprises, by weight, 700 parts of G-grade cement, 200 parts of slag powder, 50 parts of whiskers, 50 parts of polymer fibers, 50 parts of fly ash, 50 parts of microsilica powder, 50 parts of nano-styrene-butadiene latex toughening agent, 50 parts of dispersant, 60 parts of fluid loss reducer, 30 parts of expansion agent, 50 parts of early strength agent, 20 parts of defoamer and 5 parts of retarder, and is obtained by the following method: In the first step, required amounts of whiskers and polymer fibers are respectively mixed with water to obtain a whisker suspension with a mass concentration of 5% and a polymer fiber suspension with a mass concentration of 2.0%; The second step is to add water to the required amount of fluid loss reducer, nano-styrene butadiene latex toughening agent and defoamer to mix to obtain a mixed emulsion; The third step is to add the whisker suspension, the polymer fiber suspension and 55 parts of water into the mixed emulsion at a stirring rate of 4000 r / min and mix them evenly to obtain a mixed wet material; wherein the mass concentration of the solute (fluid loss reducer, nano-styrene butadiene latex toughening agent and defoaming agent) in the mixed emulsion is 15%; The fourth step is to add the required amount of Grade G cement, slag powder, fly ash, microsilica powder, dispersant, expansion agent, early strength agent and retarder to the mixed wet material in sequence at a stirring rate of 6000r / min, mix them evenly, and then stir for 5 minutes at a stirring rate of 12000r / min to obtain cement slurry that is resistant to high temperature and carbon dioxide corrosion.
[0044] Embodiment 17: The nano-styrene butadiene latex toughening agent comprises, by weight, 50 parts of styrene, 20 parts of 2-acrylamide-2-methylpropane sulfonic acid, 50 parts of polybutadiene, 15 parts of modified nano-silicon dioxide, 3.0 parts of sodium dodecyl sulfate, 1.5 parts of initiator and 0.8 parts of dodecyl mercaptan, and is obtained by the following method: S1, mixing the required amount of styrene, 2-acrylamide-2-methylpropane sulfonic acid and water to obtain a temperature-resistant monomer pre-emulsion; wherein the mass concentration of the monomers (styrene and 2-acrylamide-2-methylpropane sulfonic acid) in the temperature-resistant monomer pre-emulsion is 25%; S2, mixing the required amount of polybutadiene, modified nano-silica and water to obtain a toughening monomer pre-emulsion; wherein the mass concentration of the monomers (polybutadiene and modified nano-silica) in the toughening monomer pre-emulsion is 25%; S3, mixing a required amount of dodecanethiol with water to obtain a dodecanethiol solution with a mass concentration of 1%, adding 5% of the heat-resistant monomer pre-emulsion accounting for the total weight of the heat-resistant monomer pre-emulsion and 5% of the toughening monomer pre-emulsion accounting for the total weight of the toughening monomer pre-emulsion to the dodecanethiol solution with a vector concentration of 1%, mixing, reacting at 60° C. for 0.5 h, to obtain an emulsion seed; S4, adding the remaining amount of the temperature-resistant monomer pre-emulsion, the remaining amount of the toughening monomer pre-emulsion and the required amount of ammonium persulfate to the emulsion seed, mixing, and reacting at 65° C. for 4 hours to obtain a reaction product; S5, washing the reaction product with anhydrous ethanol, drying, and crushing to obtain a nano-styrene-butadiene latex toughening agent.
[0045] The high temperature resistant and carbon dioxide corrosion resistant cement slurry comprises, by weight, 650 parts of G-grade cement, 150 parts of slag powder, 30 parts of whiskers, 30 parts of polymer fibers, 30 parts of fly ash, 30 parts of microsilica powder, 30 parts of nano-styrene-butadiene latex toughening agent, 30 parts of dispersant, 45 parts of fluid loss reducer, 20 parts of expansion agent, 35 parts of early strength agent, 15 parts of defoamer and 2 parts of retarder, and is obtained by the following method: In the first step, required amounts of whiskers and polymer fibers are respectively mixed with water to obtain a whisker suspension with a mass concentration of 4% and a polymer fiber suspension with a mass concentration of 1%; The second step is to add water to the required amount of fluid loss reducer, nano-styrene butadiene latex toughening agent and defoamer to mix to obtain a mixed emulsion; The third step is to add the whisker suspension, the polymer fiber suspension and 50 parts of water into the mixed emulsion at a stirring rate of 4000 r / min and mix them evenly to obtain a mixed wet material; wherein the mass concentration of the solute (fluid loss reducer, nano-styrene butadiene latex toughening agent and defoaming agent) in the mixed emulsion is 10%; The fourth step is to add the required amount of Grade G cement, slag powder, fly ash, microsilica powder, dispersant, expansion agent, early strength agent and retarder to the mixed wet material in sequence at a stirring rate of 6000r / min, mix them evenly, and then stir for 3 minutes at a stirring rate of 12000r / min to obtain cement slurry that is resistant to high temperature and carbon dioxide corrosion.
[0046] The high temperature resistant and carbon dioxide corrosion resistant cement slurries prepared in Examples 15 to 17 of the present invention have good construction performance. The initial consistency of the high temperature resistant and CO2 corrosion resistant cement slurry system is ≤30Bc, and the thickening time of the high temperature resistant and CO2 corrosion resistant cement slurry can be arbitrarily adjusted within 2h to 6h in an environment of 120°C. Good flow properties can be maintained during the thickening time. The time for the high temperature resistant and CO2 corrosion resistant cement slurry to reach a consistency of 40Bc to 100Bc is less than 10min.
[0047] Example 18: The high temperature resistant and carbon dioxide corrosion resistant cement slurry prepared in Example 17 of the present invention was evaluated for toughening performance according to the method specified in GB / T19139-2012 "Test Methods for Oil Well Cement". The indicators for toughening performance evaluation include compressive strength (MPa) and elastic modulus (GPa). The results are shown in Table 1. It can be seen from Table 1 that the high temperature resistant and carbon dioxide corrosion resistant cement slurry of the present invention can effectively improve the compressive strength and elastic modulus of cement paste, and improve the mechanical properties of cement paste.
[0048] Example 19: The high temperature resistant and carbon dioxide corrosion resistant cement slurry prepared in Example 17 of the present invention was placed in a CO2 atmosphere for 0 days, 7 days, 14 days, 21 days and 30 days for corrosion resistance evaluation. The indicators for corrosion resistance evaluation include compressive strength (MPa) and permeability / mD. The results are shown in Table 2. It can be seen from Table 2 that the high temperature resistant and carbon dioxide corrosion resistant cement slurry of the present invention effectively prevents long-term CO2 corrosion from increasing the permeability of cement stone, slows down the corrosion effect of CO2 on the pores and interior of cement stone, and has strong corrosion resistance.
[0049] In summary, the high temperature resistant and carbon dioxide corrosion resistant cement slurry prepared with nano-styrene butadiene latex toughening agent as raw material in the present invention can improve the strength of the first and second bonding surfaces of the cement ring, reduce the permeability of cement stone, prevent carbon dioxide from corroding the cement stone, and at the same time increase the elastic toughness of cement stone, and reduce the degree of fracture of cement stone in subsequent cementing operations such as perforating and fracturing.
[0050] The above technical features constitute the embodiments of the present invention, which have strong adaptability and implementation effect. Non-essential technical features can be added or reduced according to actual needs to meet the requirements of different situations.
Claims
1. A nano-styrene-butadiene latex toughening agent, characterized in that The raw materials include 20 to 70 parts of styrene, 5 to 30 parts of 2-acrylamide-2-methylpropane sulfonic acid, 20 to 70 parts of polybutadiene, 5 to 20 parts of modified nano-silica, 0.5 to 5.0 parts of sodium dodecyl sulfate, 0.5 to 3.0 parts of initiator and 0.2 to 1.0 parts of molecular weight regulator in parts by weight.
2. The nano-styrene-butadiene latex toughening agent according to claim 1, characterized in that Obtained as follows: S1, mixing required amounts of styrene, 2-acrylamide-2-methylpropanesulfonic acid and water to obtain a temperature-resistant monomer pre-emulsion; S2, mixing required amounts of polybutadiene, modified nano-silica and water to obtain a toughening monomer pre-emulsion; S3, mixing a required amount of molecular weight regulator with water to obtain a molecular regulator solution, adding a portion of the temperature-resistant monomer pre-emulsion and a portion of the toughening monomer pre-emulsion to the molecular regulator solution, mixing and reacting to obtain an emulsion seed; S4, adding the remaining amount of the temperature-resistant monomer pre-emulsion, the remaining amount of the toughening monomer pre-emulsion and the required amount of the initiator to the emulsion seed, mixing and reacting to obtain a reaction product; S5, washing the reaction product with anhydrous ethanol, drying, and crushing to obtain a nano-styrene-butadiene latex toughening agent.
3. The nano-styrene-butadiene latex toughening agent according to claim 2, characterized in that The molecular regulator is dodecanethiol, and the initiator is one of ammonium persulfate, potassium persulfate, sodium persulfate and acetic anhydride; or / and, in step S1, the mass concentration of the monomer in the temperature-resistant monomer pre-emulsion is 15% to 40%; or / and, in step S2, the mass concentration of the monomer in the toughening monomer pre-emulsion is 15% to 45%.
4. The nano-styrene-butadiene latex toughening agent according to claim 2 or 3, characterized in that In step S3, a portion of the temperature-resistant monomer pre-emulsion accounts for 4% to 6% of the total weight of the temperature-resistant monomer pre-emulsion, a portion of the toughening monomer pre-emulsion accounts for 4% to 6% of the total weight of the toughening monomer pre-emulsion, and the mass concentration of the molecular regulator solution is 1%; or / and, in step S3, the reaction time is 0.4h to 0.6h, and the reaction temperature is 55°C to 65°C; or / and, in step S4, the reaction time is 3.5h to 4.5h, and the reaction temperature is 60°C to 70°C.
5. The method for preparing a nano-styrene-butadiene latex toughening agent according to claim 1, 3 or 4, characterized in that Proceed as follows: S1, mixing required amounts of styrene, 2-acrylamide-2-methylpropanesulfonic acid and water to obtain a temperature-resistant monomer pre-emulsion; S2, mixing required amounts of polybutadiene, modified nano-silica and water to obtain a toughening monomer pre-emulsion; S3, mixing a required amount of molecular weight regulator with water to obtain a molecular regulator solution, adding a portion of the temperature-resistant monomer pre-emulsion and a portion of the toughening monomer pre-emulsion to the molecular regulator solution, mixing and reacting to obtain an emulsion seed; S4, adding the remaining amount of the temperature-resistant monomer pre-emulsion, the remaining amount of the toughening monomer pre-emulsion and the required amount of the initiator to the emulsion seed, mixing and reacting to obtain a reaction product; S5, washing the reaction product with anhydrous ethanol, drying, and crushing to obtain a nano-styrene-butadiene latex toughening agent.
6. A cement slurry resistant to high temperature and carbon dioxide corrosion prepared by using the nano-styrene butadiene latex toughening agent as claimed in any one of claims 1 to 4 as one of the raw materials, characterized in that The raw materials include, by weight, 600 to 700 parts of G-grade cement, 100 to 200 parts of slag powder, 10 to 50 parts of whiskers, 10 to 50 parts of polymer fibers, 10 to 50 parts of fly ash, 10 to 50 parts of microsilica powder, 10 to 50 parts of nano-styrene-butadiene latex toughening agent, 10 to 50 parts of dispersant, 30 to 60 parts of fluid loss additive, 10 to 30 parts of expansion agent, 20 to 50 parts of early strength agent, 10 to 20 parts of defoaming agent and 0 to 5 parts of retarder.
7. The high temperature resistant and carbon dioxide corrosion resistant cement slurry according to claim 6, characterized in that Obtained as follows: In the first step, required amounts of whiskers and polymer fibers are respectively mixed with water to obtain whisker suspensions and polymer fiber suspensions; The second step is to add water to the required amount of fluid loss reducer, nano-styrene butadiene latex toughening agent and defoamer to mix to obtain a mixed emulsion; The third step is to add the whisker suspension, the polymer fiber suspension and 40 to 55 parts of water into the mixed emulsion under stirring and mix them evenly to obtain a mixed wet material; The fourth step is to add the required amount of G-grade cement, slag powder, fly ash, microsilica powder, dispersant, expansion agent, early strength agent and retarder to the mixed wet material in sequence under stirring, mix evenly, and then after high-speed stirring, obtain cement slurry that is resistant to high temperature and carbon dioxide corrosion.
8. The high temperature resistant and carbon dioxide corrosion resistant cement slurry according to claim 7, characterized in that In the first step, the mass concentration of the whisker suspension is 3% to 5%, and the mass concentration of the polymer fiber suspension is 0.5% to 2.0%; or / and, in the second step, the mass concentration of the solute in the mixed emulsion is 8% to 15%.
9. The high temperature resistant and carbon dioxide corrosion resistant cement slurry according to claim 7 or 8, characterized in that In the third step, the stirring rate is 4000 r / min during stirring; or / and, in the fourth step, the stirring rate is 6000 r / min during stirring, and the stirring rate is 12000 r / min during high-speed stirring, and the stirring time is 1 min to 5 min.
10. A method for preparing high temperature resistant and carbon dioxide corrosion resistant cement slurry according to claims 6, 8 and 9, characterized in that Proceed as follows: In the first step, required amounts of whiskers and polymer fibers are respectively mixed with water to obtain whisker suspensions and polymer fiber suspensions; The second step is to add water to the required amount of fluid loss reducer, nano-styrene butadiene latex toughening agent and defoamer to mix to obtain a mixed emulsion; The third step is to add the whisker suspension, the polymer fiber suspension and 40 to 55 parts of water into the mixed emulsion under stirring and mix them evenly to obtain a mixed wet material; The fourth step is to add the required amount of G-grade cement, slag powder, fly ash, microsilica powder, dispersant, expansion agent, early strength agent and retarder to the mixed wet material in sequence under stirring, mix evenly, and then after high-speed stirring, obtain cement slurry that is resistant to high temperature and carbon dioxide corrosion.
Citation Information
Patent Citations
Powdered latex toughening agent with good dispersibility as well as preparation method and application thereof
CN113278106A
Carbon dioxide corrosion resistant cement paste in well cementation and preparation method thereof
CN114133172A
Elastic particle for cement paste, elastic cement paste as well as preparation method and application of elastic cement paste
CN115140961A